Communication Bridge: A pilot feasibility study of Internet‐based speech–language therapy for individuals with progressive aphasia. Issue 4 (13th September 2016) - Rogalski, Emily J.; Saxon, Marie; McKenna, Hannah; Wieneke, Christina; Rademaker, Alfred; Corden, Marya E.; Borio, Kathryn; Mesulam, M.‐Marsel; Khayum, Becky
Abstract: Introduction: Individuals with aphasia symptoms due to neurodegenerative disease are under‐referred for speech–language therapy (SLT) services. We sought to determine the feasibility of utilizing telepractice, via Internet videoconferencing, to connect individuals with progressive aphasia to a speech–language pathologist (SLP) for treatment. Methods: Participants received an initial evaluation, 8 person‐centered Internet‐based SLT sessions, and 2 post‐therapy evaluations. The feasibility of providing Web‐based SLT, strategies used and their compliance, functional gains, and the duration of benefit were assessed. Results: Thirty‐four participants from 21 states and Canada were enrolled. Thirty‐one participants completed the 6‐month evaluation. SLP‐assessed and self‐reported functional gains and increased confidence in communication were documented at 2 months and maintained at 6 months postenrollment. Discussion: Internet‐based SLT using person‐centered interventions provides a feasible model for delivering care to individuals with dementia and mild and/or moderate aphasia symptoms who have an engaged care‐partner and prior familiarity with a computer.